Class Division in “12th Fail” Movie: Marxism Theory - Dita Diandra S. Arrienza; Muhammad Kiki Wardana (Mathematics Education Study Program, 2025)
This research explores the representation of social class division in “12th Fail” movie using Marxism theory approach. The movie shows the struggle of individuals from the lower class in facing an unequal education system as a reflection of social inequality in society. This research aims to find out the representation of social classes such as the bourgeoisie, middle class, and proletariat, as well as how the class struggle is depicted through characters and storylines. In addition, this research also uses the concept of base and superstructure from Karl Marx, where the base refers to the economic structure acts as the foundation of social life and production, while the superstructure including institutions such as culture, law, education, and ideology that supports and maintains the existing class structure. In the context of “12th Fail”, the movie illustrates how limited economic access (base) impedes educational opportunities, and how schools, the legal system, and social norms (superstructure) uphold systemic inequalities. The method used is descriptive qualitative with literature study, through the analysis of dialog, character interaction, and visual narration in the movie. The research concludes that “12th Fail” movie reflects the core of Marxism theory, showing that education can be both a tool of domination and social emancipation. This analysis contributes to a deeper understanding of class issues in literature, and confirms that movie can be a medium for social criticism and awareness.